THE EFFECT OF CUSTOMER WATER METER CALIBRATION IN CONTROLLING LOSS LEVELS NON-PHYSICAL WATER TIRTAULI PDAM TOZAI INDAH LAMA RESIDENTIAL AREA PEMATANGSIANTAR CITY - Pakpahan, Romauli; Frimpong Oppong, Richard; Mareny, Riada; Lubis, Josep (Universitas Efarina, 2020)
The water meter is a tool used to calculate the volume of water distributed by PDAM (Regional Water Supply Company) to customers, so that the amount to be paid can be determined. Measuring the level of accuracy of the customer's water meter aims to analyze the level of deviation of water volume measurements by water meters that occur in the field. This study is intended to analyze the effect of water meter calibration on the level of non-physical water loss. The research was conducted on 88 house connections in the Tozai Indah Lama area, Pematangsiantar City by comparing the readings of the customer's water meter with a 20 liter volume vessel. This study covers the relationship between the level of accuracy of the water meter and water loss. From the research results, the level of water loss has decreased from the beginning5.87 %become5.32 %. to the total water loss rate.